Комуністична Партія України у період перебудови: особливості діяльності у західноукраїнських областях (1985-1991 рр.) - Murawśkyj, Ołeh (Komunizm: System - Ludzie - Dokumentacja, 2013)
Untrained reform of „perestroika” has profound ideological crisis of the Communist Party of Ukraine in 1985–1991. As a result, there has been complete loss of control over social and political processes. The authority of the Communist Party undermining the newly created „informal” organizations and political parties whose activities led to a breach of the monopoly of Communist Party, and the formation of a multiparty system. Crisis could not be avoided to unsatisfactory work of the apparatchiks of primary organizations (especially large industrial enterprises).